Knowledge and use of mathematical language in initial teacher training in mathematics - Hernández-Suárez, César Augusto; Prada-Núñez, Raúl; Gamboa-Suárez, Audin Aloiso (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article analyses the levels of knowledge and use of mathematical language that students possess and employ during their initial teaching training for the program of mathematics in a Colombian public university. The research specifically proposes to establish the level of knowledge and use of mathematical language among these students, what level of math skills they use and their competence to communicate in writing their knowledge. The research design is descriptive and in field, where a sample group of 92 students from an initial teacher training program who were enrolled in subjects of discipline axis of Maths were taken into consideration. On the basis of the written problem solving level, the knowledge and use of mathematical language used by students was determined. The results show ignorance and misuse of language and mathematical symbols, rules of logic and reasoning are limited, which creates difficulties in understanding and solving mathematical problems. It was also determined that students have greater difficulties in translating the everyday language to formal, in identifying mathematical objects and work with concepts that merit logical demonstrations. Students also have an insufficient level of knowledge and use of mathematical language, a low mathematical ability and more competition to decipher the mathematical language to verbal than verbal language to encrypt mathematical language.